European Women and Preindustrial Craft - Hafter, Daryl M. (Indiana University Press, 1995)
These essays examine key eighteenth- and nineteenth-century European industries-the production of verdigris, linen, and silk; spinning, weaving, lacemaking, embroidery; calico painting; and the lingerie trade. Focusing on links between women's preindustrial craft production and nineteenth-century heavy industrialization, this volume shows how women adopted new technology in certain situations and rejected it in others, helping maintain social peace during profound economic dislocation. The contributors are Reed Benhamou, Pierre Caspard, Walter Endrei and Rachel P. Maines, Daryl M. Hafter, Inger Jonsson, Tessie P. Liu, Jean H. Quataert, Patrizia Sione, John F. Sweets, and Whitney Walton.